Credit channel and investment behaviour in Austria: a micro-econometric approach - Maria Teresa Valderrama (European Central Bank (ECB), 2001)
Using individual firm data, this study analyzes the credit channel in Austria. The estimation is based on an accelerator specification of investment demand augmented by the liquidity ratio and a firm specific user cost of capital. The results show that there is a credit channel in Austria affecting all firms, while the interest rate channel is significant as long as the liquidity ratio is not included in the regression. Taking into account trade credit or lending relationships increases the significance but not necessarily the size of the interest rate channel. The interest rate channel is not significant for young firms due mainly to the fact that young firms rely more heavily on sales to increase investment. In general it is found that firms can reduce the sensitivity of investment to their liquidity position by building lending relationships with a housebank or using trade credit as a substitute for bank loans
Keywords: C23; D92; E22; E52; G31; G32; 330; credit channel; investment demand; panel data